Comparison of Three-Port and Four-Port Laparoscopic Cholecystectomy: A Clinical Intervention Study - Torun, Mehmet (Scientific Reports in Medicine, 2025)
Objective: This study compares the outcomes of 3-port and 4-port laparoscopic cholecystectomy, evaluating differences in demographic factors, pain management, operative time, hospital stay, and recovery time. Methods: Conducted as a retrospective, randomized controlled study, data were gathered from 120 patients who underwent cholecystectomy at Van Başkale State Hospital. Patients were randomized into 3-port (n=60) and 4-port (n=60) groups. Preoperative antibiotic prophylaxis with cefazolin and postoperative pain management with diclofenac sodium were standardized. Variables analyzed included gender, surgical priority, VAS scores at 12 and 24 hours, operative time, hospitalization duration, and days to return to normal activities. Statistical significance was set at p<0.05. Results: Gender distribution differed significantly between the groups, with a higher percentage of females in the 4-port group (p=0.013). No significant differences were found in surgical priority (p=0.673), 12-hour (p=0.788) and 24-hour (p=0.532) VAS pain scores, operative time (p=0.299), or time to return to normal activity (p=0.279). However, hospital stay was significantly shorter in the 3-port group (p=0.003), suggesting a recovery advantage for this technique. Conclusion: Both 3-port and 4-port laparoscopic cholecystectomy techniques provide similar postoperative pain relief, operative efficiency, and recovery times. The 3-port technique demonstrated an advantage in reducing hospital stay, which may benefit healthcare resources and patient satisfaction. These findings support the feasibility of using the 3-port technique as a viable alternative to the 4-port approach, especially in settings prioritizing cost efficiency. Further research with larger samples and multicenter designs is needed to confirm these results and explore quality-of-life outcomes in cholecystectomy patients.